A fekvési járadék és a földértékelés kapcsolatáról - Nagy, Lajos (Tér és Társadalom, 1988)
Locational rent has come into prominence nowadays with the requirement of the thrifty use and the protection of natural (and economic) resources. In Hungary it is also necessary to analyse the role of locational rent in the differentiation of entreprise income from land use. Three points are dealt with in the paper: In Marx's land rent theory there are two fields where locational rents play a role: in colonies where land is abundant) and in the order of which land is taken into cultivation. Marx also pointed out that progress in societal production leads to two contrasted tendencies, both to equalization and differentiation, in land rents. Locational rent in the socialism is not regarded as a productive force given by nature but as an objective factor which affects expenditures, income and profit. The paper touches upon the specific features of locational rent within socialism and states that they only change on the long run and both physical and economic factors take part in their evolution. There are factors which increase and others which decrease locational rent also in the socialist economy. Transportation expenditures have a major impact on the formation of locational rent. They have three components: transportation expenditures related to supply, to marketing and to production. The paper also deals with the relationship between locational rent and land eyaluation. It discusses the proportion of locational rent within land income and the impact of various transportation costs, taken in a wide sense, on locational rent. Finally, the paper suggests an approach to locational rent on the basis of differentiation in transportation costs and transport profits among spatial units. Statistical surveys and calculations would make it possible to correct land income on the basis of locational rent.